Discussing ChatGPT in education: A literature review and bibliometric analysis - Pradana, Mahir; Elisa, Hanifah Putri; Syarifuddin, Syarifuddin (Cogent education, 2023)
This article aims to provide a review of existing research on the use of OpenAI ChatGPT in education using bibliometric analysis and systematic literature review. We explored published articles to observe the leading contributors to this field, the important subtopics, and the potential study in the future. We discovered that there is already a rise in the quantity of articles published on this subject between 2022 and 2023. We also map the research clusters using network analysis. The results obtained found a total of 93 articles. The analysis conclude that keywords such as "challenge," "teaching," and "knowledge," have not been thoroughly researched This article contributes to the literature discussing the use of artificial intelligence in education and can be useful for academics and policymakers in education.